Survival after left ventricular assist device implantation correlates with a novel device-based measure of heart rate variability: the heart rate score. (24th May 2021) - Czermak, Thomas; Seitelberger, Valentina; Hagl, Christian; Samson-Himmelstjerna, Patrick-Nicolas; Groß, Sven; Sadoni, Sebastian; Heyn, Oliver; Kellnar, Antonia; Hartrampf, Bonnie; Lemmermöhle, Eric; Klier, Ina; Rehms, Raphael; et al.
Abstract: OBJECTIVES: The heart rate score (HRS) serves as a device-based measure of impaired heart rate variability and is an independent predictor of death in patients with heart failure and a cardiac implantable electrical device. However, no data are available for predicting death from the HRS in patients with end stage heart failure and a left ventricular assist device. METHODS: From November 2011 to July 2018, a total of 56 patients with a pre-existing cardiac implantable electrical device underwent left ventricular assist device implantation at our 2 study sites. The ventricular HRS was calculated retrospectively during the first cardiac implantable electrical device follow-up examination following the index hospitalization. Survival during follow-up was correlated with initial HRS. RESULTS: During the follow-up period, 46.4% of the patients ( n = 26) died. The median follow-up period was 33.2 months. The median HRS after the index hospitalization was 41.1 ± 21.8%. More patients with an HRS >65% died compared to patients with an HRS <30% (76.9% vs 14.4%; P = 0.007). CONCLUSIONS: In our multicentre experience, survival of patients after an left ventricular assist device implant correlates with the HRS. After confirmation of our findings in a larger cohort, the effect of rate-responsive pacing will be within the scope of further investigation.